Language Skills Enhancement of Elementary School Student by Application of Integrated Learning - Hartati, Hartati (Universitas Negeri Semarang, 2017)
The purpose of this study, to improve the quality of Indonesian language learning through integrated learning approach based contextual. This type of research uses classroom action research stages of planning, implementation, observation and reflection. The experiment was conducted in two cycles, each cycle two meetings. The subject of research in the form of teachers and students of fifth grade elementary school in Ngaliyan Karanganyar subdistrict, Semarang. The results showed an increase in the quality of Indonesian language learning through integrated learning approach. This was evidenced acquisition mean the observation of teachers skills have increased the percentage of the cycle I obtained a score of 3, increasing to 3.7 in the second cycle, the activity of students in the first cycle obtained an average score of 24.36 increased to 32.27 in the second cycle, Indonesian learning outcomes aspects of reading comprehension Civics material on the first cycle 62% students pass the study, and 89% in the second cycle, aspects of the material makes social studies interview questions about the economy in first cycle, 57% students pass the study, in the second cycle to 84%. Assessment of speaking aspect in the first cycle 63% students pass the study, the second cycle to 89%. Assessment of learning outcomes aspects of writing a summary of the interview on the first cycle 57% students pass the study and 84% in the second cycle.